Kerala's Agricultural Labourers :Victims of a Crisis - S Mohanakumar (Economic & Political Weekly EPW may 10, 2008, 2008)
Most of the relief packages to tackle the farm crisis do not cover agricultural labourers, who largely belong to scheduled castes and scheduled tribes. This article analyses the situation of agricultural labourers in the crisis-affected districts of Kerala - Wayanad, Idukki and Palakkad. It also reviews the performance of the welfare schemes for agricultural labourers which are implemented through the Agricultural Workers Welfare Fund Board